Wronged by empire : post-imperial ideology and foreign policy in India and China - Miller, Manjari Chatterjee, 1976- (Studies in Asian security., 2013)
Miller uses colonialism as a lens to understand the foreign policy of countries that have undergone it, focusing specifically on the cases of India and China. Colonialism, although a hugely influential phenomenon, has not been treated systematically by IR theorists, or used to understand foreign policy decisions. This book argues that colonialism should be viewed through the lens of trauma to understand why it continues to matter to many countries today. It specifically focuses on two countries with very different colonial experiences but with a similar emphasis on their colonial past.